Risk Factor Analysis of Cataracts in Primary Health Center - Choirunisa, Latifatu; Firdausi, Asri Ayu; Hasan, Hengky Tri Cahyono; Amarusmana, Mohammad (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2024)
Introduction: Cataracts are still one of the causes of blindness worldwide. Indonesia is known for the highest cataract prevalence in Southeast Asia. Therefore, early detection is vital to slow the progression of visual impairment caused by cataracts, thereby increasing the quality of life, especially in the elderly. We aimed to analyze risk factors of cataract incidence at the Sumberasih Public Health Center. Method: A retrospective analytical study was conducted with a total of 100 samples that were divided equally into a cataract group and a control group. The data was analyzed using the SPSS program. Result: A majority of cataract subjects are women (62%), pre-elderly (40%), working exposed to UV sun rays (60%), cigarette smoke (78%), and having abnormal body mass index (58%). We found that gender, UV exposure based on occupation, hypertension history, cigarette smoke exposure, and body mass index were significantly correlated to cataract incidence, respectively, p = 0.009, p = 0.016, p = 0.037, p < 0.001, and p = 0.045. The Chi-square test results p < 0.025 were followed by logistic regression, and gender was the most influential risk factor of cataract incidence, approximately 4.050 times (CI 95%: 1.427 - 11.498). Conclusion: Cataracts can be caused by several risk factors. Hopefully, risk factors discovered as early as possible can reduce the risk of developing cataracts.